2018
DOI: 10.1016/j.tate.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Changing approaches to classroom assessment: An empirical study across teacher career stages

Abstract: Research indicates that there is considerable variability in teachers' approaches to assessment resulting in different learning cultures for students. The primary purpose of the study is to examine the relationship between teachers' approaches to assessment across a set of dimensions (including their conceptions of assessment purposes, processes, fairness, and measurement theory) and career stage. The results of this paper illustrate nuanced impacts of career stage on teachers' approaches to multiple dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 48 publications
2
54
0
1
Order By: Relevance
“…One of the essential purposes of assessment as learning is that students should become the protagonists of their learning (Coombs et al 2018;DeLuca et al 2016). This means tutors must assume more of a role as facilitator.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…One of the essential purposes of assessment as learning is that students should become the protagonists of their learning (Coombs et al 2018;DeLuca et al 2016). This means tutors must assume more of a role as facilitator.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The findings of these studies indicated that the teachers might not have been well prepared to assess student learning and they had low assessment knowledge for implementing the high-quality assessment. Particularly, pre-service teachers had limited assessment capabilities (Coombs, 2018;Cowan, 2009;DeLuca & Klinger, 2010;MacLellan, 2004;Volante & Fazio, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even within a single teacher education programs, there can be variability between assessment education courses, suggesting that while there is a dominant policy discourse on K-12 assessment within provinces, there remains variable learning and interpretations of the policy. Furthermore, teacher candidates within the same cohort have significant variability in knowledge and attitudes toward assessment (Volante and Fazio, 2007;DeLuca and Klinger, 2010;Coombs et al, 2018). Despite the presence of consistent teacher accreditation practices, evidence suggests a fairly weak classification of assessment knowledge as prescribed by teaching standards within Canada, which may contribute to variable assessment education models and outcomes for teacher candidates.…”
Section: Canadamentioning
confidence: 99%